2016
DOI: 10.1186/s12889-016-3043-8
|View full text |Cite
|
Sign up to set email alerts
|

How equitable are community health worker programmes and which programme features influence equity of community health worker services? A systematic review

Abstract: BackgroundCommunity health workers (CHWs) are uniquely placed to link communities with the health system, playing a role in improving the reach of health systems and bringing health services closer to hard-to-reach and marginalised groups. A systematic review was conducted to determine the extent of equity of CHW programmes and to identify intervention design factors which influence equity of health outcomes.MethodsIn accordance with our published protocol, we systematically searched eight databases from 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(136 citation statements)
references
References 50 publications
5
126
0
5
Order By: Relevance
“…Similarly, both wealth and education were negatively associated with coverage, which again may be explained by a higher probability of poor health among the socioeconomically disadvantaged. Overall, it is thus plausible that the RHM programme reduces social inequities in access to health care in Swaziland similar to what a recent systematic review has found to be the case for several other CHW programmes in LMICs . A limitation of this study is that we are unable to disentangle the reasons for which RHMs were more likely to visit households that were poor and less educated.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Similarly, both wealth and education were negatively associated with coverage, which again may be explained by a higher probability of poor health among the socioeconomically disadvantaged. Overall, it is thus plausible that the RHM programme reduces social inequities in access to health care in Swaziland similar to what a recent systematic review has found to be the case for several other CHW programmes in LMICs . A limitation of this study is that we are unable to disentangle the reasons for which RHMs were more likely to visit households that were poor and less educated.…”
Section: Discussionmentioning
confidence: 51%
“…Such contexts most typically include countries with large rural populations and/or with overextended and under-resourced human resources for health (HRH). The use of CHWs in such areas is thought to be a key strategy for increasing horizontal equity in access to health care between rural and urban populations as well as between individuals from different socio-economic backgrounds [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…no. reviews contributing termsReviews contributing terms‘Place’Place of residence5No-5No-5[1014]‘Race’Race / ethnicity / culture / language3Yes →69No-9[11, 1522]Occupation6No-6No-6[11], [13], [16], [23], [24], [25]‘Gender’Gender / sex1Yes →67No-7[16], [17], [18], [19], [26], [27], [28]Religion0Yes →11Yes →23[17, 29, 30]Education7No-7No-7[11, 13, 16, 24, 25, 31, 32]‘SES’Socio-economic status12No-12No-12[11], [13], [15], [23], [24], [25], [31], [32], [33], [34], [35], [36]Social capital0Yes →11Yes →45[17, 3740]Other category not encompassed by PROGRESS-Plus6No-...…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the three principles and five building blocks enable programs to help health systems best reach the three dimensions of Universal Health Coverage: (1) coverage, (2) scope of services, and (3) financial protection. In addition, they add a very important focus on equity, highlighting the imperative for well-designed CHW programs to reach the most vulnerable [26].…”
Section: The Analytical Frameworkmentioning
confidence: 99%